Teachers and Students’ Perceptions of Communicative Competence in English as A Foreign Language in Indonesia - Hery Yufrizal (Bandar Lampung University (UBL), 2014)
This article is a part of attempts to formulate and design a comprehensive rationale in formulating standard of communicative competence of English for Indonesian EFL learners. The study focuses on the perceptions of students and teachers on what communicative competence means, and how they perceive each component of the communicative competence of English.This research is a quantitative research concentrating on finding out the perceptions of students and English teachers on communicative competence in Indonesia. The subjects consist of 31 English teachers of junior and high schools in Bandar Lampung, 37 non English Language Teaching (non-ELT) students, and 56 English Language Teaching (ELT) Students. Fifty questions are designed to find out the teachers’ and students’ perception of communicative competence and its components. The questions were grouped into five categories: definition of communicative competence, linguistic competence, sociolinguistic competence, discourse competence, and strategic competence.Through ANOVA statistical analysis, it was founds English teachers’ perceptions on definition of communicative competence and strategic competence were not significantly different from non English Language Teaching (non-ELT) students and ELT students. Teachers differed significantly in perceiving the linguistic, sociolinguistic, and discourse competence from that of non ELT and ELT students